MANAJEMEN DISPENSASI NIKAH DI ERA PERATURAN NIKAH USIA 19 TAHUN - Nurahma Fanny; Sepna Lisarianti; Masyhari (IAIC (Institut Agama Islam Cirebon), 2021)
ABSTRACK In cases that are under the authority of the religious courts, there are several cases that are closely related to the rights of children, including the case of applying for a marriage dispensation. Marriage dispensation is a voluntary case in the form of concessions given by the court to prospective husbands and wives who have not reached the lowest age limit of 19 years. According to Article 7 paragraph (1) of Law no. 16 years old, boys and girls are 19 years old. However, if a man and a woman are less than 19 years old, their marriage is considered invalid by the State. If you are in an emergency situation, such as pregnant, afraid of adultery, embarrassed because you are not married, afraid of things that are prohibited by religion. Aims to find out the application of Law NO 16 of 2019. The results of the study explain that the panel of judges considers and makes a very fair decision to decide whether it is appropriate for a couple who applies for a dispensation to get a marriage dispensation. taking into account the circumstances of the two prospective brides both in terms of economic, social, health and others.